Toward Cross-Border Engineering Management: Development and Test of a Practice for Idea Generation in Customer–Supplier DFM Teams. Issue 4 (2nd October 2017) - Vesalainen, Jukka; Thorgren, Sara; Rossi, Timo
Abstract: Growing inter-organizational dependence within business ecosystems necessitates more intensive cooperation between various organizational functions, not only sales and purchasing. Engineering management is one of the functions typically regarded as an in-house activity. Prior research acknowledges certain cooperative forms such as early supplier involvement, but it falls short on identifying practices of grass-roots level cooperation. However, it is the quality of the interaction between supplier and customer that is decisive if the advantages of collaboration are to materialize. This study aims to fill this obvious gap in both theory and practice by developing and testing an inter-organizational practice for co-ideation in a supplier-customer relationship. Specifically, a way of working for idea generation to improve inter-organizational learning within specific Design for Manufacturing meetings between an industrial corporation and two of its important suppliers is developed. The evaluation of the tested co-ideation practice indicated that, in comparison to the traditional way of working, the new practice contributed to a greater number of generated ideas, was found useful in practice, and expert ratings suggested that the ideas generated were of adequate quality. The implication for practice is the proposed procedure that aims to build a safe psychological environment and help participants to transcend existing behavioral roles as representatives of suppliers and customers.